STRATEGI KOMUNIKASI KUDAIRENG DALAM MEMPERSIAPKAN KADER DA’I DI PESANTREN TEBUIRENG JOMBANG - Arifah Qolbiyah; Suhari Suhari (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research analyzes the communication strategy of Kudaireng organization in preparing da'I cadres in Tebuireng Jombang pesantren. This type of research is qualitative using organizational communication theory. The focus of this research are: (1) How is Kudaireng's communication strategy in preparing da'I cadres at the Tebuireng Jombang pesantren? (2) What are the supporting and inhibiting factors of Kudaireng's organizational communication in the process of preparing da'I cadres at the Tebuireng Jombang pesantren? This study has the following objectives; (1) To find out and describe the organizational communication strategies that Kudaireng has in preparing da'I cadres at the Tebuireng Jombang pesantren, (2) To find out and analyze the supporting and inhibiting factors of Kudaireng's organizational communication in the process of preparing da'I cadres at the Tebuireng Jombang pesantren. This research is also descriptive because it describes theories and opinions related to organizational communication strategies that are applied. In this study, the object of research is Kudaireng's organizational communication strategy in preparing da'I cadres at Tebuireng Islamic Boarding School. The research subjects are the coaches, administrators, and members of Kudaireng in Tebuireng Jombang Islamic boarding school.